'If a leaf falls, they blame the tree' 1: scattered notes on Gezi resistances, contention, and space - Karasulu, Ahu (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2014)
On 31 May 2013, violent police intervention against the activists at Gezi Park, Istanbul, resisting against the unlawful demolition of trees at the park, led to a popular uprising throughout Turkey. It was unexpected and unprecedented. The resistances were, and still are, multifaceted and multilayered. Taken as an episode of contention, it is hard to argue that this has come to an end, and the falling leaf can hardly be blamed on the tree. This paper is an attempt to understand this episode, borrowing from the DOC (dynamics of contention) program, emphasizing the importance of space in the Lefebvrian sense, with respect to the changing socio-spatial order of the cities.
Keywords: Gezi Park; Turkey; space; politics of contention; Sociology